(untitled) (American Journal of Technology and Applied Sciences, 2022)
This article summarizes the current technical requirements and architectural solutions for unmanned aerial vehicles (UAVs, drones) intended for three-dimensional terrain mapping (photogrammetry, LiDAR, visual-optical SLAM systems). Recommendations are provided regarding platform selection, sensors (cameras, LiDAR, IMU, GNSS/RTK/PPK), survey parameters (GSD, overlaps, trajectories), data processing (SfM–MVS, LiDAR pipelines, visual-inertial filters), and accuracy assessment.